Management of Glioblastoma Multiforme in a Patient Treated With Ketogenic Metabolic Therapy and Modified Standard of Care: A 24-Month Follow-Up - Elsakka, Ahmed M. A.; Bary, Mohamed Abdel; Abdelzaher, Eman; Elnaggar, Mostafa; Kalamian, Miriam; Mukherjee, Purna; Seyfried, Thomas N. (Frontiers in Nutrition, 2018)
Abstract Few advances have been made in overall survival for glioblastoma multiforme (GBM) in more than 40 years. Here we report the case of a 38-year-old man who presented with chronic headache, nausea, and vomiting accompanied by left partial motor seizures and upper left limb weakness. Enhanced brain MRI revealed a solid cystic lesion in the right partial space suggesting GBM. Serum testing revealed vitamin D deficiency, and elevated levels of insulin and triglycerides. Prior to sub-total tumor resection and standard of care (SOC), the patient conducted a 72-hr water-only fast. Following the fast, the patient initiated a vitamin/mineral-supplemented ketogenic diet (KD) for 21 days that delivered 900 kcal/day. In addition to radiotherapy, temozolomide chemotherapy, and the KD (increased to 1500 kcal/day at day 22), the patient received metformin (1000 mg/day), methylfolate (1000 mg/day), chloroquine phosphate (150 mg/day), epigallocatechin gallate (EGCG, 400 mg/day), and hyperbaric oxygen therapy (HBOT) (60 min/session, 5 sessions/wk at 2.5 ATA). The patient also received levetiracetam (1500 mg/day). No steroid medication was given at any time. Post-surgical histology confirmed the diagnosis of GBM. Reduced invasion of tumor cells and thick-walled hyalinized blood vessels were also seen suggesting a therapeutic benefit of pre-surgical metabolic therapy. After nine months treatment with the modified SOC and complimentary ketogenic metabolic therapy (KMT), the patient’s body weight was reduced by about 19%. Seizures and left limb weakness resolved. Biomarkers showed reduced blood glucose and elevated levels of urinary ketones with evidence of reduced metabolic activity (choline/NAA ratio) and normalized levels of insulin, triglycerides, and vitamin D. This is the first report of confirmed GBM treated with a modified SOC together with KMT and HBOT, and other targeted metabolic therapies. As rapid regression of GBM is rare following sub-total resection and SOC alone, it is possible that the response observed in this case resulted in part from the modified SOC and other novel treatments. Additional studies are needed to validate the efficacy of KMT administered with alternative approaches that selectively increase oxidative stress in tumor cells while restricting their access to glucose and glutamine. The patient remains in excellent health (Karnofsky Score,